Explain of Students Creativity Based on Spiritual Happiness with Mediating Role of Perfectionism - Moin Mehr, Farnaz; Afrooz, Gholam Ali; Davaee, Mahdi (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2023)
Background and Aim: Students’ innovative and creative thinking determines important aspects of their lives; however, environmental and personality factors affecting it, have been neglected. This study was conducted with the aim of "explaining students’ creativity on spiritual vitality with the role of perfectionism". Methods: The research was descriptive and structural equation modeling type. The statistical population of the study consisted of all male and female students studying in the undergraduate level of architecture schools in Tehran in the academic year 2020, of which 300 students (150 girls and 150 boys) were selected by cluster random sampling method. Abedi Creativity Questionnaire, Afrooz Spiritual Joy Questionnaire and Terry Short Questionnaire were used to collect data. Data analysis was performed at two levels of descriptive and inferential and with the necessary assumptions and with SPSS and AMOS software version 24 and at the significance level of 0.05. Results: Based on the results of this study, the proposed model of causal relationships between the mentioned variables had an acceptable fit. In general, in the proposed research model, the results showed that spiritual vitality is directly and indirectly related to creativity through perfectionism in students. Also, the results showed that the relationship between spiritual vitality and perfectionism is inverse and significant. Conclusion: According to the results of the research, it is suggested that the authorities, by preparing programs, in addition to increasing awareness on creativity and its development stages, have a special focus on promoting students’ spiritual vitality.